The population variable and its impact on the strength of the state (Iraq as a model) (Journal of the College of Basic Education, 2023)
Summary of the research:Human factors are one of the most important factors influencing the state. Most of the political problems that the world suffers from are mainly due to the human side. Without this factor, the effectiveness of other factors cannot be achieved. This research aims to clarify the importance of the human element and its related economic and social activities, which have a profound impact To make political decisions, and thus to the power of the state and its international standing, through what the population represents of an essential weight among the general foundations of the power of the state, as it constitutes the work force necessary to manage its affairs and develop its economy, and also provides it with the necessary human power, especially in the military aspect, and when it is exercised The population has different patterns of values and cultures that prevail in society, through which we can say that it expresses its national and patriotic will and that it would play different roles as tools of power affecting other peoples.Keywords: state power, population elements, population and development.